Fatal case of echovirus type 9 encephalitis. Issue 9 (September 1993) - Zuckerman, M A; Sheaff, M; Martin, J E; Gabriel, C M
Abstract : Enteroviruses are rare causes of acute focal encephalitis. A fatal case of echovirus type 9 infection is reported in a 9 month old boy who presented with a fever and a macular rash followed by two focal seizures. Echovirus type 9 was isolated from lung tissue after seven days.